2020
DOI: 10.3390/molecules25143181
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Orientation of Photochromic Gadolinium Oxyhydride Films

Abstract: We report preferential orientation control in photochromic gadolinium oxyhydride (GdHO) thin films deposited by a two-step process. Gadolinium hydride (GdH2-x) films were grown by reactive magnetron sputtering, followed by oxidation in air. The preferential orientation, grain size, anion concentrations and photochromic response of the films were strongly dependent on the deposition pressure. The GdHO films showed a preferential orientation along the [100] direction and exhibited photochromism when synthesized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
(55 reference statements)
2
6
0
Order By: Relevance
“…[ 2 ] The deposition pressure is inversely related to the photochromic contrast and, has been demonstrated for both YHO [ 15,20 ] and a related material, gadolinium oxyhydride. [ 21 ] The memory effect caused by consecutive darkening–bleaching cycles leads to higher photochromic contrast and faster photodarkening rates, which is consistent with the photodarkening behavior observed at 5 K. Additional experiments are needed to fully elucidate the individual effects of photodarkening temperature and deposition pressure from those due to memory on the photochromic performance. It should also be noted that the photochromic contrast in the IR spectral region where OH vibrations typically occur (3000–3500 cm −1 ) exhibits a significant Δ T at 5 K compared to the essentially null change at 295 K. Such a change might be indicative of the presence of and changes to OH‐related species, but our data do not allow us to draw a definitive conclusion at this time.…”
Section: Figuresupporting
confidence: 62%
“…[ 2 ] The deposition pressure is inversely related to the photochromic contrast and, has been demonstrated for both YHO [ 15,20 ] and a related material, gadolinium oxyhydride. [ 21 ] The memory effect caused by consecutive darkening–bleaching cycles leads to higher photochromic contrast and faster photodarkening rates, which is consistent with the photodarkening behavior observed at 5 K. Additional experiments are needed to fully elucidate the individual effects of photodarkening temperature and deposition pressure from those due to memory on the photochromic performance. It should also be noted that the photochromic contrast in the IR spectral region where OH vibrations typically occur (3000–3500 cm −1 ) exhibits a significant Δ T at 5 K compared to the essentially null change at 295 K. Such a change might be indicative of the presence of and changes to OH‐related species, but our data do not allow us to draw a definitive conclusion at this time.…”
Section: Figuresupporting
confidence: 62%
“…RBS/ERD data additionally verify that a higher deposition pressure results in a higher O/H ratio, in qualitative agreement with the progressive decrease of the refractive index, as implied by the decreasing amplitude of the thin-film interference oscillations ( Figures S2 and 1 b, top panel), and with previous studies on both Y and Gd oxyhydride thin films. 8 , 11 , 12 …”
mentioning
confidence: 99%
“…RBS/ERD data additionally verify that a higher deposition pressure results in a higher O/H ratio, in qualitative agreement with the progressive decrease of the refractive index, as implied by the decreasing amplitude of the thin-film interference oscillations (Figures S2 and 1b, top panel), and with previous studies on both Y and Gd oxyhydride thin films. 8,11,12 We argued recently that the reaction from metallic REH 2 dihydride to photochromic REO x H 3−2x oxyhydride happens in two steps: 5,13 first, a net oxygen incorporation (eq 1a); second, a continuous oxygen-for-hydrogen (1:2) exchange (eq 1b). 13…”
mentioning
confidence: 99%
“…Recently, it was found that oxygen-containing rare-earth metal hydride thin films (REHO) change their optical transmission under illumination with visible light at ambient conditions, [1][2][3][4][5] attracting the attention of the scientific community for their potential applications in the next generation of photochromic coatings (smart windows) and optoelectronic devices (gas sensors). [6][7][8] Transparent and photochromic REHO films are produced by either reactive Ar-magnetron sputtering [9] or reactive electron-beam evaporation [10] of a rareearth metal hydride (REH 2 ) onto a transparent substrate, followed by oxidation in air.…”
Section: Introductionmentioning
confidence: 99%